CENTRAL SYSTOLIC PRESSURE AND EXECUTIVE FUNCTION IN CHILDREN AND ADOLESCENTS WITH PRIMARY AND SECONDARY HYPERTENSION. (April 2021) - Stabouli, Stella; Chrysaidou, Katerina; Kotsis, Vasilios; Chainoglou, Athanasia; Gidaris, Dimos; Zafeiriou, Dimitrios
Abstract: Objective: The aims of the present study were to assess executive function performance in children and adolescents with primary and secondary hypertension and to investigate for associations with central systolic pressure and mean ambulatory blood pressure (BP) levels. Design and method: The study population included 46 pediatric patients with secondary hypertension, and 46, age and sex matched, patients with primary hypertension who underwent ambulatory BP monitoring, pulse wave analysis, and assessment of executive function using Behavior Rating Inventory of Executive Function (parent version, BRIEF, and self-reported version, BRIEF SR). Results: Patients with secondary hypertension had higher T scores in BRIEF parent metacognition (MI) (51.19 ± 8.92 vs. 47.56 ± 7.49, p < 0.05), and BRIEF-SR MI scales (49.62 ± 9.08 vs. 42.09 ± 7.88, p = 0.001) compared to primary hypertensives. The groups did not differ in means of BRIEF parent and BRIEF-SR Behavior Regulation Index (BRI) T scores, as well as day and night mean arterial pressure (MAP) z scores, prevalence of ambulatory hypertension, and pulse wave velocity (PWV) z score. However, those with secondary hypertension tented to have higher central systolic pressure (cSP) z scores (p = 0.053), and lower body mass index (BMI) z score (p < 0.001). In the ANCOVA analysis cSP z score was associated with BRIEF parent MI (B = 0.95, 95%CI 0.02–1.87, p < 0.05), and BRI T scores (B = 1.14, 95%CI 0.07–2.21, p < 0.05), and BRIEF-SR MI T score (B = 1.481, 95%CI 0.393–2.569, p < 0.05), independent of night MAP z score, age, sex, SES, hypertension group (primary/secondary), and antihypertensive treatment (yes/no). Conclusions: Central systolic pressure associates with executive function performance in hypertensive youth independent of hypertension etiology and seems to have pivotal role in the lower metacognition scores in the secondary hypertension group.